Accuracy evaluation and clinical realization of digital interproximal enamel reduction for orthodontics: a case study - Jia You; Xiangyu Zhou; Xiaofan Xia; Jianxing Zhang; Yunfeng Liu (BioMedical Engineering OnLine)
Abstract Objective This study presents a novel digital interproximal enamel reduction (IER) clinical procedure, aiming to improve the effectiveness of IER processes in orthodontic treatment. Methods A malocclusion case of skeletal-class I and angle-class I was selected for the experimental investigation. A three-dimensional (3D) model of the dentition was constructed using scanning data from a plaster model. The IER volume was measured by the overlay area of two neighboring crowns on the arranged virtual teeth. For the upper dentition, a guide plate was innovatively designed based on the original surface of the dentition and the calculated IER volume. The guide plate was fabricated using stereolithography 3D printing (SLA), and was successfully employed during the IER operation. For the lower dentition, the IER procedure was performed using the free-hand method, guided by the predesigned IER volume. Preoperative and postoperative 3D models of the dentition were compared to assess the accuracy of both IER methods. Results The standard deviation of upper dentition IER with guide plate was calculated as 0.13 mm, while that of lower dentition IER by freehand was 0.24 mm. Conclusion Through the integration of laser scanning, 3D reconstruction, virtual arrangement, guide plate design, and 3D printing, this study not only explores a novel digital IER method, but also demonstrates its clinical applicability. The findings provide compelling evidence of the method’s superior accuracy in clinical practice, offering a new approach for high-precision IER operations in orthodontic treatment.